Accountability in QS al-Fātiḥah (1:4): A Theological Framework for Ethical Conduct and Public Sector - Muslikun, Muslikun; Trisanti, Theresia; Umar, A.; Anggoro, Rusmawan Wahyu; Giri, Efraim Ferdinan; Kholil, Asyhar (Unisia, 2025)
This study examines the concept of accountability in QS al-Fātiḥah (1:4) to clarify how the verse māliki yawmid-dīn shapes moral agency, ethical consciousness, and responsible human conduct. Using a qualitative design grounded in library research, the study analyzes classical and contemporary tafsīr through the tafsīr tahlili method and synthesizes supporting scholarly literature from Islamic ethics and moral psychology. The results show that accountability in this verse reflects a comprehensive moral framework rooted in divine sovereignty and the certainty of judgment, generating values such as self-awareness, time consciousness, moral courage, and stewardship. These values influence individual behavior, guide ethical decision-making, and reinforce social and institutional responsibility. The discussion highlights convergence between classical and modern interpretations while noting empirical gaps in understanding how accountability functions in lived contexts. Overall, the study demonstrates that Qur’anic accountability is a holistic ethical structure capable of informing personal morality, educational practice, and governance. Its findings underscore the contemporary relevance of Qur’anic ethics and call for interdisciplinary empirical research to strengthen applications of accountability in diverse social settings.